2018
DOI: 10.1146/annurev-orgpsych-032117-104451
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad and Workplace Behavior

Abstract: Over the last 15 years, there has been growing fascination among scholars in studying “dark behaviors” and “dark traits,” especially as they are expressed in organizational contexts. One taxonomy of dark traits that has garnered special interest is the dark triad (DT), which is comprised of three toxic and malevolent traits: psychopathy, narcissism, and Machiavellianism. This chapter offers a review of DT research, with a particular focus on research relevant to the organizational sciences. We begin with a def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 110 publications
4
107
2
8
Order By: Relevance
“…In addition, internal psychometric structure of the SD3 is different from its predictive validity as well (Rosenthal & Rosnow, 2008, p. 115). Thus, even though current research indicates that SD3 has an unclear internal psychometric structure, our studies and others reported elsewhere (e.g., LeBreton et al, 2018; O’Boyle et al, 2012; Palmer, Komarraju, Carter, & Karau, 2017) have shown that it predicts occupational outcomes. That is, there is evidence for SD3’s predictive utility.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In addition, internal psychometric structure of the SD3 is different from its predictive validity as well (Rosenthal & Rosnow, 2008, p. 115). Thus, even though current research indicates that SD3 has an unclear internal psychometric structure, our studies and others reported elsewhere (e.g., LeBreton et al, 2018; O’Boyle et al, 2012; Palmer, Komarraju, Carter, & Karau, 2017) have shown that it predicts occupational outcomes. That is, there is evidence for SD3’s predictive utility.…”
Section: Discussioncontrasting
confidence: 74%
“…The last two decades have seen growing interest in the role of the Dark Triad traits (i.e., narcissism, psychopathy, and Machiavellianism; Paulhus & Williams, 2002) in occupational settings (LeBreton, Shiverdecker, & Grimaldi, 2018). The increasing interest in the Dark Triad personality traits has examined its association with negative vocational outcomes, such as workplace deviance and counterproductive behaviors (Grijalva & Newman, 2015; O’Boyle, Forsyth, Banks, & McDaniel, 2012).…”
mentioning
confidence: 99%
“…The finding that positive personality traits have a significant and negative effect on white-collar offending should help bolster employers' confidence in screening for characteristics such as honesty and agreeableness in the recruitment and selection of potential employees (Nikolaou & Foti, 2018). Similarly, the observed significant effects of negative personality traits are consistent with research demonstrating the connections between the "dark triad" (i.e., psychopathy, narcissism, and Machiavellianism) and a variety of problematic outcomes in organizations (LeBreton et al, 2018;Tokarev et al, 2017). Effectively managing individuals who possess these traits is likely a more challenging task than selecting for positive traits, especially given that psychopathy-at least in corporate leaders-has also been linked to business success (Boddy, 2017).…”
Section: Policy Implicationssupporting
confidence: 77%
“…Potential reasons for this finding could be that Machiavellians generally strive for agentic goals such as money and power (Christie & Greis, 1970; Wilson et al, 1996) and are especially motivated by financial goals (Jones & Paulhus, 2009). In a similar vein, Machiavellians act strategically and plan ahead (Grosz et al, 2017), which might help them to extract resources from their environment and navigate organizational politics to climb the corporate ladder (Smith et al, 2018) and might be more willing to cross lines, such as lying to get ahead in their jobs (Hogue, Levashina, & Hang, 2013; LeBreton, Shiverdecker, & Grimaldi, 2018).…”
Section: Discussionmentioning
confidence: 99%